2019
DOI: 10.1017/jfm.2019.745
|View full text |Cite
|
Sign up to set email alerts
|

Electrorheology of a dilute emulsion of surfactant-covered drops

Abstract: The effects of surfactant coating on a deformable viscous drop under the combined action of a shear flow and a uniform electric field, are investigated by solving the coupled equations of electrostatics, fluid flow and surfactant transport. Employing a comprehensive three-dimensional solution technique, the non-Newtonian shearing response of the bulk emulsion is analyzed in the dilute suspension regime. The present results reveal that the surfactant non-uniformity creates significant alterations in the flow di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…The high voltage is supplied across the electrodes and dynamics are captured by using cameras. In these studies, some authors have also introduced surfactants at the liquid-liquid interface [ 27 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. A summary of the most prominent works related to droplet EHD are summarized in Table 1 .…”
Section: Approaches Used To Study the Droplet Electrohydrodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high voltage is supplied across the electrodes and dynamics are captured by using cameras. In these studies, some authors have also introduced surfactants at the liquid-liquid interface [ 27 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. A summary of the most prominent works related to droplet EHD are summarized in Table 1 .…”
Section: Approaches Used To Study the Droplet Electrohydrodynamicsmentioning
confidence: 99%
“…The influence of interfacial properties on the droplet deformation and breakup under an electric field has also been a topic of profound interest for decades [ 27 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. The surface-active molecules prompt to change in the interracial and rheological properties, leading to interfacial perturbations and breakups [ 23 , 71 , 136 , 137 , 138 ].…”
Section: Surfactant-laden Dropletsmentioning
confidence: 99%
“…Electric field Surfactants Method References Stokes dc, uniform insoluble analytical (SD) [42] N.-S. dc, uniform insoluble numerical (LS-RegM) [43] Stokes dc, uniform insoluble (semi-) analytical (LD) [44,45] Stokes dc, uniform insoluble numerical (BIM) [46,47] Stokes dc, uniform insoluble analytical & numerical [48][49][50] Stokes dc, nonuniform insoluble analytical & numerical [51] Stokes dc, uniform soluble numerical (IIM) Present Work electrodeformation of a viscous drop [42,46,[52][53][54]. By reducing the surface tension and inducing a significant Marangoni stress due to the surfactant transport on the interface, surfactant could lead to drastically different EHD of a surfactant-laden viscous drop.…”
Section: Fluidsmentioning
confidence: 99%
“…Motivated by the classical work of Taylor (1966), several studies have been reported on electrically modulated morpho-dynamics of droplets in an external flow (Hase, Watanabe & Yoshikawa 2006; Ristenpart et al 2009; Mhatre & Thaokar 2013; Zhang et al 2016; Brosseau & Vlahovska 2017; Poddar et al 2018, 2019 b ; Behera et al 2019; Santra et al 2018 b , 2019 a ; Santra, Das & Chakraborty 2020). Mandal, Bandopadhyay & Chakraborty (2016) studied the cross-stream migration of the droplet in unbounded plane Poiseuille flow under uniform electric field.…”
Section: Introductionmentioning
confidence: 99%